ДЖАЛОЛИДДИН МАНГУБЕРДИ (Modern education and development, 2024)
В статье говорится о жизни и деятельности великого правителя государства Хорезмшахов Джалолиддина Мангуберди.Его жизнь была посвящена против нашествия монголов, возглавляемых Чингизханом и защите независимости своего государства.The article talks about the life and work of the great ruler of the Khorezmshakh state Jaloliddin Manguberdi.His life was devoted to fighting the invasion of the Mongols, led by Genghis Khan and defending the independence of his state